Shotgun and TMT-Labeled Proteomic Analysis of the Ovarian Proteins of an Insect Vector, Aedes aegypti (Diptera: Culicidae). Issue 2 (18th March 2022) - Geiser, Dawn L; Li, Wenzhou; Pham, Daphne Q-D; Wysocki, Vicki H; Winzerling, Joy J
Abstract: Aedes aegypti [Linnaeus in Hasselquist; yellow fever mosquito] transmits several viruses that infect millions of people each year, including Zika, dengue, yellow fever, chikungunya, and West Nile. Pathogen transmission occurs during blood feeding. Only the females blood feed as they require a bloodmeal for oogenesis; in the bloodmeal, holo-transferrin and hemoglobin provide the females with a high iron load. We are interested in the effects of the bloodmeal on the expression of iron-associated proteins in oogenesis. Previous data showed that following digestion of a bloodmeal, ovarian iron concentrations doubles by 72 hr. We have used shotgun proteomics to identify proteins expressed in Ae. aegypti ovaries at two oogenesis developmental stages following blood feeding, and tandem mass tag-labeling proteomics to quantify proteins expressed at one stage following feeding of a controlled iron diet. Our findings provide the first report of mosquito ovarian protein expression in early and late oogenesis. We identify proteins differentially expressed in the two oogenesis development stages. We establish that metal-associated proteins play an important role in Ae. aegypti oogenesis and we identify new candidate proteins that might be involved in mosquito iron metabolism. Finally, this work identified a unique second ferritin light chain subunit, the first reported in any species. The shotgun proteomic data are available via ProteomeXchange with identifier PXD005893, while the tandem mass tag-labeled proteomic data are available with identifier PXD028242.